New 3'‐Triazolyl‐5'‐aryl‐chalcogenothymidine: Synthesis and Anti‐oxidant and Antiproliferative Bladder Carcinoma (5637) Activity. Issue 12 (30th March 2018) - Munchen, Taiana S.; Sonego, Mariana S.; de Souza, Diego; Dornelles, Luciano; Seixas, Fabiana K.; Collares, Tiago; Piccoli, Bruna C.; da Silva, Fernanda D'Ávila; da Rocha, João Batista T.; Quoos, Natália; Rodrigues, Oscar E. D.
Abstract: This article describes the synthesis and characterization of new 3'‐triazolyl‐5'‐aryl‐chalcogenothimidyne derivatives. Sulfur, selenium, and tellurium nucleosides were prepared from commercial zidovudine, using a linear synthetic strategy affording these compounds in good yields. The respective molecules were evaluated for cytotoxicity in bladder carcinoma 5637 cells and as an antioxidant agent, showing a linear dependence on the chalcogenium atom for both biological approaches. Tellurium was the most active element, followed by selenium and sulfur. Abstract : In this study, the synthesis of a new block of nucleosides derived from zidovudine containing S, Se, and Te was disclosed. Synthesized compounds were evaluated for biological application as antioxidant and antitumoral agents against bladder carcinoma cells (5637), showing a straight connection with chalcogenium atom for both biological approaches. Tellurium was the most active element, followed by selenium and sulfur. Additionally, antitumoral selectivity was evaluated and it was possible to observe a preference in inhibiting tumor cells growth rather than healthy ones.